Implementasi Konsepsi Ke-Esaan Tuhan Dalam Tri Murti Puja di Pura Samuantiga: Perspektif Komunikasi Hindu - I Wayan Wirta; Anggara Putu Dharma Putra; Sintyananda Gayatri; Made Suta (Jayapangus Press, 2026)
The understanding of the concept of the Oneness of God among Hindu devotees is often reduced to symbolic and traditional ritual practices, resulting in a gap between Vedic theological teachings and everyday religious practice. This condition underscores the importance of studies that position Tri Murti Puja not merely as a ritual expression, but as a form of theological communication that represents the doctrine of the One Supreme God in Hinduism. This study aims to examine the concept of the Oneness of God based on Hindu sacred texts and its implementation in Tri Murti Puja practices through the perspective of Hindu communication. This research employs a qualitative approach with a descriptive-interpretative design. Data were collected through textual analysis of the Vedas, Upanishads, Puranas, and the Tri Sandhya mantra, as well as field research involving ritual observation, documentation of temple shrines (pelinggih), and interviews with temple priests and Hindu devotees at Pura Samuantiga. Data analysis was conducted inductively through processes of data reduction, categorization, and interpretation of the theological and communicative meanings of ritual practices. The findings indicate that the concept of the Oneness of God in Hinduism is consistently affirmed in Vedic teachings through the principle of Ekam Eva Advitiyam, which is symbolically implemented in Tri Murti Puja. The Tri Murti does not represent polytheism, but rather a differentiation of divine functions within a single transcendent reality. Ritual practices such as Ngambeng, Nampyog, and Siat Sampian function as media of religious communication that transmit theological, ethical, and social values to the community. Rituals serve as a system of signs that bridge abstract understandings of divine unity with concrete religious experience. This study confirms that Tri Murti Puja constitutes an effective form of Hindu communication in internalizing the doctrine of the Oneness of God. The integration of theological, symbolic, and communicative dimensions within ritual practices strengthens śraddhā and bhakti among devotees while ensuring the continuity of Hindu teachings within the local cultural context. The originality of this study lies in its use of a Hindu communication perspective to explain Tri Murti Puja as a theological medium for expressing the concept of the Oneness of God, a perspective that has been insufficiently explored in previous studies.